Analisis Faktor-faktor Penerimaan Penggunaan Sistem Keuangan Desa: Pendekatan TAM dan TPB - Naila Rizki Salisa; Ida Nur Aeni; Ahmad Abdul Chamid (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2019)
This study aims to analyze factors that influence the use of Siskeudes and examines which model that appropriate to investigates the factors of acceptance the use of Siskeudes. This study uses two models, namely Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). Research data was obtained through questionnaires distributed to respondents. The samples of this research were 82 respondents that use Siskeudes in each Kudus District Government. Data were analyzed using Structural Equation Modellling (SEM) with path analysis method. The results show that the factors of both model, both TAM and TPB can explain the acceptance of using Siskeudes. However, perceived ease of use and perceived behavioral control have no significant effect on actual use of Siskeudes. TAM model was found to be able to investigate the acceptance factors of using Siskeudes quite well than TPB model. Although, both model hasn’t difference value.